Seasonal Assessment of Aquatic Avifauna of Nal Sarovar Sanctuary, Gujarat, India - Joshi, K.; Tatu, K.; Kamboj, R. D. (Indian Forester, 2020)
A study was conducted by Gujarat Ecological Education and Research (GEER) Foundation on waterbirds of Nai Sarovar Sanctuary during the years 2016-18 covering all the majorseasons. A total of 85 waterbird species were recorded that belonged to 18 families. Among all the families, maximum number of species (14 species, i.e.16% of all the waterbird species) were represented by Anatidae family[i.e., the family of ducks, geese and swans] followed by those of Scoiopacidae family [i.e., the family ofsandpipers, shanks, snipes, stints, curlews etc.; (12 species, 14%)]. The study has also indicated that the Sanctuary supported maximum number ofspecies ofwaterbird during winterseason (84 species), whereas minimum number of waterbird species were recorded in summer (50 species). The study has indicated that Nal Sarovar has highest utility as waterbird habitat during winter season therefore maximum management practices should be focused during this period.